INCORPORATION OF ALKALINE-EARTH METALS Ca, Mg, Ba and Sr IN MCM-41 FOR APPLICATION AS CO2 ADSORVENTS IN THE PRE-SALES NATURAL GAS CURRENTS - Thaís Regina Silva Ribeiro; David Clebson de Melo Silva; Tiago Pereira Martins da Costa; Antonio Osimar Sousa da Silva (The Journal of Engineering and Exact Sciences)
The new oil fields discovered in the Pre-Salt Province have large oil reserves, but the technological challenges for their economic exploitation are enormous. One of the problems with these reservoirs is that the associated gas has high concentrations of carbon dioxide, which must be removed and disposed of properly. In this way it is necessary to develop technologies for the separation of CO2 from natural gas streams, but there is a complication for these new technologies; the fact that they must be able to treat currents with relatively high concentrations of carbon dioxide. In the present project, the alkaline-earth cations Ca, Mg, Ba and Sr in the molecular sieve MCM-41 will be impregnated for adsorption in natural gas streams, as this modification will provide the formation of acid sites favoring the adsorption reaction.